Stochastic Liouville equations for coherent multidimensional spectroscopy of excitons - Sanda, Frantisek; Mukamel, Shaul (The journal of physical chemistry. B, 2008)
Signatures of chemical exchange and spectral diffusion in 2D photon-echo line shapes of molecular aggregates are studied using model calculations for a dimer whose Hamiltonian parameters are stochastically modulated. Cross peaks induced by chemical exchange and by exciton transport have different dynamics and distinguish two models which have the same absorption spectrum (a two-state jump bath modulation model of a dimer and a four-state jump bath model of a single chromophore). Slow Gaussian-Markovian spectral diffusion of a symmetric dimer induces new peaks which are damped as the dipole moment is equilibrated. These effects require an explicit treatment of the bath and may not be described by lower-level theories such as the Redfield equations, which eliminate the bath.
Keywords: normální rozdělení; spektrální analýza; stochastické procesy; Models, Chemical; dimerizace; chemické modely; Spectrum Analysis; Dimerization; Normal Distribution; Photons; difuze; fotony; Diffusion; Stochastic Processes; Time Factors; časové faktory